2018
DOI: 10.28992/ijsam.v2i1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corporate Governance on Environmental Disclosure of Listed Non-Financial Firms in Nigeria

Abstract: The study investigates the influence of corporate governance on environmental disclosure of non-financial firms listed in Nigeria Stock Exchange (NSE), anchoring on “trinity theory” (agency, stakeholder and legitimacy theories). 86 firm-year observations across 86 companies listed in Nigeria Stock Exchange (NSE) using content analysis, cross-sectional data, OLS regression techniques were used to analyze the influence of board characteristics on the extent of overall environmental disclosure (OED). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 91 publications
(144 reference statements)
6
46
0
1
Order By: Relevance
“…Past studies have indicated that big firms even though they are endowed with more resources as well as earning higher profits (Swastika, 2013), normally adopt discretionary reporting frequently as compared to the smaller firms (Barako and Brown, 2006;Khodadadi, Khazami, and Aflatooni, 2010). The firm financial strength was preferred due to its significant influence on the quantity of overall ecological disclosure of several firms (Odoemelam and Okafor, 2018). This supports the study's application of the financial strength as the moderating variable.…”
Section: Financial Strengthsupporting
confidence: 73%
See 2 more Smart Citations
“…Past studies have indicated that big firms even though they are endowed with more resources as well as earning higher profits (Swastika, 2013), normally adopt discretionary reporting frequently as compared to the smaller firms (Barako and Brown, 2006;Khodadadi, Khazami, and Aflatooni, 2010). The firm financial strength was preferred due to its significant influence on the quantity of overall ecological disclosure of several firms (Odoemelam and Okafor, 2018). This supports the study's application of the financial strength as the moderating variable.…”
Section: Financial Strengthsupporting
confidence: 73%
“…This implies that South African legal and regulatory framework (IR) is strong which substituted the degree of South Africa ecological reporting while the non-executive board of directors in Nigeria listed firms compensated for the poor regulatory environment (Adegbite, 2015). In the same vein, Odoemelam and Okafor (2018) justified the stakeholder theory on the basis that in an ecology coupled with weak legal and institutions, more of whole-time service directors will ensure stakeholders protection of their interest. Contrary to the findings is by Akbas (2016), whose results found no statistically significant association between the degree of ecological reporting and board independence.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased awareness of social, environmental and governance issues has greatly transformed the way business is conducted (Seuring & Müller, 2008;Kolk & van Tulder, 2010;Odoemelam & Okafor, 2018) as corporations are increasingly pressured to report on additional issues such as governance, social responsibility and intellectual capital (Rodríguez-Ariza et al, 2012). Corporate boards are the ultimate decision making unit in a firm, with power and responsibility for overseeing affairs and have a significant influence on corporate strategy (Lynall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many are not having the neccassary business background yet aged 50 years and above. This thus makes their role in the supervision of and performance for the company, both financial and non-financial performance, limited (Maryati, 2018;Dewi, 2014, Debby, et al, 2014Siahaan, 2013;Agustina, 2017;Adeniyi & Fadipe, 2018;Odoemelam & Okafor, 2018).…”
Section: Introductionmentioning
confidence: 99%